#TITLE_ALTERNATIVE# - Sesa (NIM 202 98 010), Elisa
Abstract : Measurement on the magnetic characteristics is very important in analyzing magnetic samples for some applications such as recording materials, permanent magnets, and other industrial materials. There are several instruments available to analyze the magnetic characteristic of samples, including a hysteresis loop tracer. This instrument gives several characteristic parameters such as coercivity, saturation field, and magnetic remanence. We have designed a new type of hysteresis loop tracer based on a rotating pick-up coil. The rotating pick-up coil is placed inside a magnetic field generated by an electromagnet. The emf in the pick-up coil (without a sample) indicates the strength of the magnetic field. However, by placing a sample inside the pick-up coil, the emf will depends also on the sample. By subtracting the emf produced by the pick-up coil with a sample from the emf produced without a sample and plot them as a function of magnetic field, one can obtain a hysteresis loop. The system consists of three major parts, namely the transducer and mechanical systems, the conditioning and signal processor circuits and the personal computer as data processor and display system. The transducer and mechanical systems include an electromagnet, power supply, pick-up coil, sample holder, and a DC electric motor. The conditioning and signal processor circuits include precision rectifier, ADC, optical sensor, DAC, and micro-controller. The relative error for the strength of magnetic field was found to be 0.03% to 1.42% while that for the serial communication system was 0.01% to 0.22%. The measurement without sample gives a relative error from 0.01% to 2.21%. Measurements using several known magnetic materials show promising results. Depending on their mineralogy and grain size distribution, the hysteresis curve from one sample to another shows differently.